Konstruksi Delik dalam Tradisi Ngomo dan Merari' Tau Samawa sebagai Perbuatan yang Tidak Dipandang sebagai Tindak Pidana dalam Sistem Hukum Adat - Jasardi Gunawan; Dianto (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
The recognition of living law under Article 2 of Indonesian Law Number 1 of 2023 on the Criminal Code marks a paradigm shift from formal legality toward acknowledging laws that exist within society. However, previous studies have primarily emphasized legal pluralism, customary law recognition, and the legality principle, while limited attention has been given to how indigenous communities construct criminality. This study analyzes the delict construction underlying the Ngomo and Merari' Tau Samawa traditions, which may formally satisfy the elements of theft and kidnapping under positive criminal law but are not regarded as criminal acts within customary legal systems. Using a Systematic Literature Review (SLR) based on the PRISMA 2020 guidelines, this research synthesizes evidence through qualitative content analysis and conceptual comparison. The findings identify five key parameters shaping customary delict construction: social legitimacy, mutual consent, social purpose, customary control mechanisms, and restorative orientation. The study proposes the Living Law Delict Construction Framework (LLDCF), offering a conceptual model that bridges formal legality and social legality in developing a more pluralistic and culturally responsive Indonesian criminal law.